Study of ELISA and antibiotic sensitivity test for Salmonella enteritidis as experimental infection in mice - Baghdad Science Journal (مجلة بغداد للعلوم, 2009)
Salmonella enteritidis one of more important as epidemiological bacteria between other salmonella types. It is very important pathologically that cause food poising and gastrointestinal tract infections. This study includes some of immunological changes that appear by ELISA test and antibiotic sensitivity test against these bacteria in mice. ELISA test results appears high immunological response happen after 3 days of inoculation, mean titration readings beginning 0.198 and the maximum mean titration after 15 days of inoculation 1.538 and begin to decrease after this time slowly to remain about 0.297 after 40 days of inoculation. An antibiotics sensitivity test result appears, this bacteria sensitive to Chloramphenicol, Ceftriaxone, Ciprofloxacin and Cotrimaxazol. Resistance to Neomycin, Streptomycin and Rifampicin, while intermediate against Ampicilin and Amoxicillin. Another test we use Vitek system to know bacterial sensitivity against to more another types of antibiotics and to confirm between some of them.